2021
DOI: 10.1186/s12885-021-08267-9
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of male triple-positive breast Cancer patients: a propensity score matched SEER analysis and molecular portraits

Abstract: Background The purpose of this study was to explore clinicalpathology features, molecular features and outcome of male breast cancer patients who expressed ER, PR as well as HER-2, namely triple-positive male breast cancer (TP-MBC), and compared them with triple-positive female breast cancer patients (TP-FBC). Methods TP-MBC and TP-FBC from 2010 to 2017 were selected from the Surveillance, Epidemiology, and End Results database (SEER). Kaplan-Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Compared to ER-PR-HER2+ breast cancer, TPBC is less invasive and HER-2 expression levels are lower (30). Among all TNBC patients, male patients have a higher aggressiveness and are more likely to have metastases than female patients (31). Trastuzumab is a key treatment strategy for TPBC patients and is also the first-line treatment option for relapsed and metastatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ER-PR-HER2+ breast cancer, TPBC is less invasive and HER-2 expression levels are lower (30). Among all TNBC patients, male patients have a higher aggressiveness and are more likely to have metastases than female patients (31). Trastuzumab is a key treatment strategy for TPBC patients and is also the first-line treatment option for relapsed and metastatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumor staging is an important factor affecting the survival and prognosis of tumor patients [17][18][19], especially with respect to distant metastasis, which is the main cause of death of these cancer patients. The study of Wang et al [20] showed that the T, N and M stages were prognostic factors for MBC patients. However, our study suggested that only the T and M stages affected the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…23 Wang et al showed in their study, in which they compared triple-negative male and female patients using the SEER database, that the prognosis was worse in triple-negative male breast cancer patients than female patients, and it was suggested that this might be due to tumoral and individual genetic differences between the two groups. 24 The difference in epidemiological risk factors and tumor biology is one of the most important reasons for the difference in the prognosis and treatment of breast cancer in males and females. 14 As shown in our study, hormone receptor positivity is a better prognostic indicator in females, while it is associated with a poor prognosis in males.…”
Section: Discussionmentioning
confidence: 99%